Association between serum miRNAs and gingival gene expression in an obese rat model. (2nd March 2022) - Maruyama, Takayuki; Kobayashi, Terumasa; Sugiura, Yoshio; Yoneda, Toshiki; Ekuni, Daisuke; Morita, Manabu
Abstract: Introduction: Recent studies have reported a relationship between periodontitis and obesity; however, the mechanisms of obesity's effects on periodontitis are not well understood. On the other hand, microRNAs (miRNAs) are known to play key roles in the post‐transcriptional regulation gene expression by suppressing translation and protein synthesis. We examined the association between obesity‐related miRNAs and gene expression in gingival tissue using miRNA–messenger RNA (mRNA) pairing analysis in an obese rat model. Methods: Sixteen male Wistar rats aged 8 weeks old were divided into two groups: the control group was fed a normal powdered food for 8 weeks, and the obesity group was fed a high‐fat diet for 8 weeks. Distance from the cement–enamel junction to the alveolar bone crest of the first molars was measured. miRNA microarray analysis was performed on samples of serum and gingival tissue; the resulting data were used to calculate fold changes in miRNA levels in the obesity group relative to the control group, and miRNA–mRNA pairing analysis was performed to identify mRNAs potentially targeted by miRNAs of interest. Results: Alveolar bone loss in the obesity group exceeded that in the control group ( p = .017). miRNA–mRNA pairing analysis identified an association between 4 miRNAs ( miR ‐ 759, miR ‐ 9a ‐ 3p, miR ‐ 203b ‐ 3p, and miR ‐ 878 ) that were differentially expressed in the obesity and control groups and 7 genes ( Ly86, Arid5b, Rgs18, Mlana, P2ry13, Kif1b, and Myt1 ) expressed in gingival tissue. Conclusion: This study revealed that several miRNAs play an important role in the mechanism of periodontal disease progression induced by the obesity.